Back to Russian monolingualism? Discursive reflections on the 2017 educational reform in Russian- and Tatar-language media - Gimadieva, Alfinaz; Warditz, Vladislava (Frontiers in Language Sciences, 2025)
AimsThis paper examines recent developments in Russian-language policy through a case study of the Republic of Tatarstan, with a focus on the abolition of compulsory Tatar-language instruction in 2017. Previous studies predominantly analyzed Russian-language media; our study aims to explore how this policy shift has been discursively framed and contested in both Russian- and Tatar-language media. Positioned within broader discussions of language ideologies in multilingual and post-imperial contexts, the study examines how such reforms reflect enduring tensions between centralizing state narratives and regional demands for linguistic and cultural recognition. Drawing on theoretical insights from Critical Discourse Studies and language ideology research, the paper examines how media discourses shape and reflect the ideological landscape of bilingualism and minority language rights in the Russian Federation.MethodsUsing a qualitative Critical Discourse Analysis approach, we analyse a corpus of 42 articles−20 from Russian-language and 22 from Tatar-language online media outlets—published in response to the 2017 educational reform. These sources were selected to represent the most prominent discursive reactions to the abolition of mandatory Tatar-language instruction in schools. The analysis focused on identifying evaluative language, argumentation strategies, and thematic framing of the policy change. Articles were coded for stance (positive, negative, neutral) and categorized by themes such as cultural identity, legal arguments, educational rights, and national unity. The study draws on CDA frameworks (Fairclough, van Dijk, Blommaert). It applies the Sociology of Knowledge Approach to Discourse to uncover how underlying ideologies and power relations inform media representations of language policy. The comparative analysis enables an examination of divergent narratives between linguistic communities.ResultsThe findings reveal a stark contrast in the discursive framing between Russian- and Tatar-language media. Tatar-language outlets predominantly emphasize the symbolic and cultural significance of Tatar instruction, framing the reform as a threat to ethnic identity and linguistic heritage. In contrast, Russian-language media tend to highlight legal compliance, civic unity, and educational pragmatism, positioning the reform as a step toward reinforcing national cohesion and equality. These divergent perspectives illustrate how language policies are deeply embedded in ideological struggles over identity, power, and statehood. The study demonstrates that public debates in Tatarstan are not merely about language instruction but about competing visions of federalism, minority rights, and the role of regional languages in the post-Soviet space. This case study underscores the tense and fluctuating nature of language relations in post-imperial contexts like Russia, where historical legacies of both linguistic empowerment and suppression continue to shape contemporary policy debates. The findings contribute to a broader understanding of how language ideologies are constructed and contested in multilingual states, highlighting the need for more balanced research that incorporates both dominant and minority language perspectives.